Lightweight Technology on the Barrel of Tank - 李程;毛保全;冯帅 (东华大学学报（英文版）, 2017)
In order to solve the problem of the large weight about the barrel of tank, a lightweight method of tank gun based on the pressure anisotropy characteristics of magnetized plasma sheath was put forward. Compared with the traditional tank gun, the radial pressure was greatly reduced because of the existence of the plasma sheath, which reduced the requirement of tank material. It provided the possibility of using super light metal as the material of barrel, and it could solve the contradiction between light weight and large power of tank gun.